(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The direction of trade flows, which includes both exports and imports, has a significant impacton the global economy. This abstract gets to the heart of what international commerce is and how itaffects the economies of different nations. When a country buys anything made in another country, it issaid to have imported that commodity or service. A country’s economic growth is proportional to itstrade surplus or deficit. Trade agreements and global supply chains also have a significant impact ontrade flows, which in turn promotes economic development and specialization. In today’s increasinglylinked and globalized world, an appreciation of trade patterns is crucial to making sense of economicdynamics.